2015
DOI: 10.1007/s00464-015-4244-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic appendectomy and cholecystectomy versus open: a study in 1999 pregnant patients

Abstract: While fetal events are unknown, LA and LC in pregnant patients demonstrated shorter ORT, LOS, and reduced complications and were performed more frequently over time. Even in perforated cases, laparoscopy appears safe in pregnant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 63 publications
1
52
0
4
Order By: Relevance
“…[26] Some authors state that even in perforated cases, laparoscopy appears safe in pregnant patients. [27] There are also some limitations to use of laparoscopic appendectomy such as instance of diffuse peritonitis, advanced pregnancy with markedly enlarged uterus, or lack of experience of the surgeon or operating team. [13] In the present study, laparoscopic appendectomy was performed in 20% of all patients without any complication; thus, we also believe that it is a safe and feasible approach for pregnant women with appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Some authors state that even in perforated cases, laparoscopy appears safe in pregnant patients. [27] There are also some limitations to use of laparoscopic appendectomy such as instance of diffuse peritonitis, advanced pregnancy with markedly enlarged uterus, or lack of experience of the surgeon or operating team. [13] In the present study, laparoscopic appendectomy was performed in 20% of all patients without any complication; thus, we also believe that it is a safe and feasible approach for pregnant women with appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies with 10,632 patients (1219 open, 9413 laparoscopic) were included (Table 1) [18][19][20][21][22][23][24][25][26][27][28]. All studies examined populations from the United States of America and were retrospective comparative studies.…”
Section: Study Demographicsmentioning
confidence: 99%
“…All studies examined populations from the United States of America and were retrospective comparative studies. Two studies were based on national databases [18,19], one study was state based database [20], while the remaining studies were single or multi-institution studies [21][22][23][24][25][26][27][28]. Data collection ranged between 1980 and 2012 with minimal or no overlap of data between the national, state and the institutional studies.…”
Section: Study Demographicsmentioning
confidence: 99%
“…[1][2][3] The most common non-obstetric cause for abdominal pain is acute appendicitis which has an incidence of 1 in 1500 pregnancy which is similar to the incidence in nonpregnant population. 4,5 It has been reported that maternal morbidity in acute appendicitis without perforation is 17% compared with 52% with perforation while fetal mortality in noncomplicated appendicitis is 7% compared with 24% in cases with complicated appendicitis. [6][7][8] In general, laparoscopic appendectomy is considered nowadays as the standard technique for treating acute appendicitis but this can be stated for non-pregnant women as in pregnant women doing laparoscopic appendectomy still having debates about its safety for both fetus and mother.…”
Section: Introductionmentioning
confidence: 99%